Southey the Epic-Headed - Tucker, Herbert (Romanticism on the Net, 2003)
AbstractDubious though the honour may be, if anybody dominated the anglophone epic poetry scene across the Romantic period it was Robert Southey. For forty years he was at work on one or another extended verse narrative, with topics that represented, on four continents, cultures from medieval Christendom, Islam, Hindustan, and the indigenous New World. Between the two quite different versions of Joan of Arc that he published in 1796 and 1837 appeared Thalaba the Destroyer (1801), Madoc (1805), The Curse of Kehama (1810), Roderick, the Last of the Goths (1814), and A Tale of Paraguay (1825). Southey’s chosen themes of contest and conquest threw into high relief the profile of each culture he seized on, as in a different register did his characteristically bookish and condescending notes. Enlightened skepticism about alien systems of belief, joined to antinomian indifference to the internal logic of social patterns, disposed Southey’s epics to forms of causal overdrive that impoverish their narrative interest, even as they fulfill a whole set of now widely discredited clichés about Romantic alienation, transcendence, unstoppable will and insatiable desire. To Southey’s known importance for his Laker contemporaries, and his impact on Byron and Shelley in the next generation, may be added an extensive legacy to Victorian verse and prose narrative art: an influence that is the stranger given the extremity of his example. Action after action in Southey’s epic poems illustrates the incompatibility with heroic virtue of any course of action – i. e., any plot – that does not result in personal, national, or (at the imaginative bedrock these slighter levels imply) cosmic catastrophe.